Profitability, asset investment, and aggregate stock returns - Chue, Timothy K.; Xu, Jin Karen (Journal of Banking & Finance, 2022)
We find that aggregate profitability and asset investment exhibit robust joint predictive power for aggregate excess stock returns, consistent with the investment model of Hou, Xue, and Zhang (henceforth HXZ, 2015). These results provide out-of-sample empirical support for HXZ, as the same mechanisms that HXZ use to explain firm-specific variation in stock returns can also be used to explain variation that is market-wide in nature. Also consistent with the HXZ investment model, we find that the growth rate of short-term (long-term) assets exhibits a stronger predictive power for one-year-ahead (two-year-ahead) stock returns.